Aftermath of the CFA Franc Devaluation - Cosse, Stephane (Occasional Papers; Occasional Paper, 1996)
Developments in the countries of the CFA franc zone in the aftermath of the January 1994 devaluation of the CFA franc are reviewed in this paper. Following a summary of the new adjusment strategy, the papers describes the progress made and the difficulties encountered during 1994 and early 1995 in implementing the programs supported by use of IMF resources.